Littering in Mankweng Zone A : a situational waste management study - Tivani, Chucheka Lawrence (My University, 2004)
The purpose of this study was to first determine the nature and magnitude of littering in Mankweng Zone A, through observation and from the views of not only the Local Municipality (LM) which is in charge of waste management but also from the views of the Mankweng community that do the littering – the residents, street vendors, shop business owners, taxi drivers and passengers. The object of this was to determine the views of all the above stakeholders about what should be done to minimise the littering problem. Such an approach of involving the community in the identification of the causes of environmental problems has been found to be useful in coming up with sustainable community-generated solutions. The findings of the study acknowledged that the widespread littering in Mankweng Zone A is unacceptable and therefore needs addressing. Also, and more importantly, the reasons for the wide spread littering were suggested and the roles which the LM and the Mankweng community could and should play in minimizing littering were also suggested. These were used as a basis for recommendations made to the LM as the overseer of the good health of the environment. These included the adequate provision of litter bins in all areas where people congregate for either social or economic reasons, the regular removal of litter from households and the daily removal of waste from the Central Business District, the involvement of the community in waste management campaigns and the promulgation of waste management by- laws by the LM and the involvement of the community members in enforcing such by- laws. Finally it was recommended that since the taxi drivers insist that the passengers litter the environment rather than their taxis, the taxi drivers be encouraged to carry plastic litter bags in which passengers would drop litter rather than throw such litter through the taxi windows.
Thesis (M. Phil. (Environmental Law and Management)) -- University of Limpopo, 2004
Keywords: Littering; Situational Waste; Management; Refuse and refuse disposal; Waste disposal in the ground; Litter (Trash)